2016
DOI: 10.1038/srep29796
|View full text |Cite
|
Sign up to set email alerts
|

Strip-Pattern-Spheres Self-Assembled from Polypeptide-Based Polymer Mixtures: Structure and Defect Features

Abstract: We found that poly(γ-benzyl-L-glutamate)-block-poly(ethylene glycol) (PBLG-b-PEG) rod-coil block copolymers and polystyrene (PS) homopolymers can cooperatively self-assemble into nano-spheres with striped patterns on their surfaces (strip-pattern-spheres) in aqueous solution. With assistance of dissipative particle dynamics simulation, it is discovered that the PS homopolymers form a spherical template core and the PBLG-b-PEG block copolymers assemble into striped patterns on the spherical surface. The hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…studied the cooperative self‐assembly of a chiral rod‐coil BCP poly(γ‐benzyl‐L‐glutamate)‐ block ‐poly(ethylene glycol) (PBLG ‐b ‐PEG) and homopolymer PS into colloidal particles with striped patterns on their surfaces (strip‐pattern‐spheres). [ 65 ] Recently, the 3D soft confinement of chiral BCP polystyrene‐ block ‐poly( d ‐lactide) (PS ‐b ‐PDLA) was reported. [ 66 ] Although colloidal particles with patterned surfaces were obtained, this study mainly investigated the effect of a kinetic parameter, the solvent evaporation rate, on the morphology of colloidal particles, while the effect of chirality was not intensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…studied the cooperative self‐assembly of a chiral rod‐coil BCP poly(γ‐benzyl‐L‐glutamate)‐ block ‐poly(ethylene glycol) (PBLG ‐b ‐PEG) and homopolymer PS into colloidal particles with striped patterns on their surfaces (strip‐pattern‐spheres). [ 65 ] Recently, the 3D soft confinement of chiral BCP polystyrene‐ block ‐poly( d ‐lactide) (PS ‐b ‐PDLA) was reported. [ 66 ] Although colloidal particles with patterned surfaces were obtained, this study mainly investigated the effect of a kinetic parameter, the solvent evaporation rate, on the morphology of colloidal particles, while the effect of chirality was not intensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…[100,104,105] Also, the same group demonstrated the co-assembly of PEG-b-PBLG/PEG-b-PBDG BCPs* with PS homopolymers into spherical assemblies with striped topologies. [106,107] It was found that chiral spiral patterns were obtainable from PEG-b-PBLG/PS and PEG-b-PBDG/PS, whereas an achiral meridian-like pattern was obtained from PEG-b-PBLG/PEG-b-PBDG/PS. These works highlighted the significance of the molecular and conformational chirality of BCPs* to the morphological chirality of assemblies, and enriched the formation of spiral assemblies.…”
Section: Self-assembly Of Bcps* In Selective Solventsmentioning
confidence: 99%
“…For an ordered dot surface nanopattern, the dot array characteristics are an essential aspect that should be discussed. [37,38] For spherical particles on a flat substrate, it is well known that the ideal packing mode is a sixfold coordinated lattice, i.e., the particles take the form of domain with six nearest neighbors. [39] However, in practice, due to the imperfect shape of spherical particles, the patterns usually contain other array modes, typically fivefold coordinated lattices that are characterized by +1 disclinations and sevenfold coordinated lattices that are characterized by −1 disclinations.…”
Section: Introductionmentioning
confidence: 99%